Повышение достоверности принятия решений при распознавании образов - Мамедов, Р.К.; Иманова, У.Г. (Электронное моделирование, 2014)
Разработана методика принятия решений по распознаванию образов с учетом закона распределения погрешностей измерения признаков образов. Поскольку распознавание эталонного образа и распознаваемого означает совпадение их признаков, мера близости должна максимально отражать количественную оценку совпадающих и несовпадающих признаков. Розроблено методику прийняття рішень по розпізнаванню образів на основі закону розподілення похибок вимірювання ознак образів. Оскільки розпізнавання еталонного образу та образу, що розпізнається, означає співпадіння їх ознак, міра близькості повинна максимально відображати кількісну оцінку співпадаючих та неспівпадаючих ознак. The paper describes the importance of improving the recognition reliability by reducing the measurement errors of the parameters. The errors, which can be minimized by statistical processing of the measurement results, are the most dangerous. However, this reduces the system speed of response. The article considers the existing formulas for estimating a measure of proximity between objects, which do not allow for the facts of coincidence of individual traits and depend mainly on the distance between the non-matching attributes of objects. Since the recognition of different images is the coincidence of their signs, the measure of closeness as possible should reflect the quantitative assessment of matching and non-matching features. The decision-making method is based on pattern recognition, taking into account the distribution of errors in the measurement attributes of images.